Teaching English to Young Learners in India: English Classes Pratham Education - Muhammad Ari Saputra Muhammad Ari Saputra; Rizky Yolanda (Journal of English Education and Linguistics, 2020)
There is now a growing tendency among Indonesian people to introduce English to children starting from the early age, through either formal or informal education. This can be seen from the mushrooming of bilingual and international schools where English is used as the language of instruction as well as the increasing number of English courses aimed especially for children. Sometimes people hold a misconception regarding teaching English for young learners, in which they believe that the earlier the kids learn a foreign language, the better it will be. As a matter of fact, this assumption is not completely true. Only when handled with care will the teaching of foreign language to young learners succeed as expected? Otherwise, this will not gain a significant effect on children’s language development. This paper will elaborate some principles on how young learners learn a foreign language, which should be the foundation of the way the teaching English to young learners is conducted. Some theories on how children learn will be drawn on, followed by a discussion on the pedagogical implications. This paper is expected to give insights to English teachers in general and teachers of English for young learners in particular, about the importance of taking into account the aspects related to the way young learners learn in designing their teaching learning process.